Development of Chemo-Entrepreneurship Book Entitled “Peduli Lokal, Melek Global”: Popularizing Chemistry and Developing Life Skills in Industrial Revolution Era 4.0 - Khairiatul Muna (Unib Press, 2022)
The entrepreneurship course in Chemistry Education or Tadris Kimia study program at three universities in South Kalimantan (Universtias Islam Negeri Antasari Banjarmasin, Universitas Lambung Mangkurat (ULM), and Universitas Islam Kalimantan Muhammad Arsyad Al Banjari Banjarmasin (UNISKA)) has not integrated chemistry studies. In addition, there is also no chemo-entrepreneurship book that can be used as a reference in the entrepreneurship course. Therefore, a Research and Development (R&D) was carried out to develop a chemo-entrepreneurship book on local care and global literacy as an effort to popularize chemistry and develop life skills in the industrial revolution era 4.0. The book was developed using the Borg and Gall model with the modification of the study steps only to the limited trial stage. Based on the results, the book (chemo-entrepreneurship book entitled “peduli lokal, melek global”) is very valid and feasible to use (revision according to suggestions), besides being practical with a good linguistic aspect.